INVERTER PWM UNTUK MENGGERAKKAN MESIN ARUS SEARAH TANPA SIKAT BERBASIS ARDUINO - Sony Prakarsa Putra; Zulwisli Zulwisli (Universitas Negeri Padang, 2019)
This study aims to create a PWM inverter that can drive the Brushless Unidirectional Flow Machine (MASTS). PWM inverters are intended to correct deficiencies in six-step inverters. Inverter is a circuit that is used to convert a DC voltage source into an AC voltage with a certain frequency. The use of inverters is found in electric vehicles. The system often used to control an inverter is a Pulse Width Modulation (PWM) based control, where pulse width is used to regulate speed. The inverter is tested using 3 pairs of mosfets as a switch to control the three-phase output of the inverter. In the inverter, PWM is used to adjust the width of the frequency pulse that will be given to the mosfet. This research used 3 variations of duty cycle 30%, 60%, 90% to determine the effect of MASTS speed on PWM by using a PWM inverter. The results of this study the speed of MASTS can be influenced by changes in duty cycle, with increasing value of the duty cycle, the faster the speed of MASTS, and vice versa. Keywords:Mosfet, Sensor Hall, MASTS, PWM, Inverter.